A rare initial presentation of a thymic neuroendocrine tumor as Cushing's syndrome. Issue 7 (9th July 2021) - Matarneh, Ahmad S.; Hamad, Abdelrahman O.; Hamad, Mohammad K.; Elouzi, Elhadi B.; Mahmood, Nabil S.; Al‐Sawalmeh, Khaled; Al‐Bozom, Issam; Hussein, Mousa S.; Yassin, Mohamed A.
Abstract: While evaluating the cause of Cushing's syndrome, biochemical confirmation should be sought first as imaging studies might misdirect the diagnosis toward the wrong problem. One of the rare secondary causes that should be kept in mind while evaluating Cushing's syndrome is the thymic neuroendocrine tumor. Abstract : While evaluating the cause of Cushing's syndrome, biochemical confirmation should be sought first as imaging studies might misdirect the diagnosis toward the wrong problem. One of the rare secondary causes that should be kept in mind while evaluating Cushing's syndrome is the thymic neuroendocrine tumor.